DESIGNING A TOOL FOR COLD KNURLING OF FINS - Olejnik, Andrej; Kapitanov, Alexey; Alexandrov, Islam; Tatarkanov, Aslan (Journal of Applied Engineering Science, 2020)
Regulating the deformed metal’s flow is an important condition for the knurling process. To achieve this, the knurling tool should have a special intake part, where all the main work of plastic deformation would be realized. Depending on the configuration, the fins can be knurled in two ways: either by a radial feed of the tool or an axial feed of a billet (package of billets) or a tool. Using the radial feed method, most types of piece gear parts can be knurled using a more rational radial flow of the deformed metal. However, this process is usually characterized by low productivity. The axial knurling method is significantly more productive. In this case, due to the undesirable axial flow of the deformed metal, it flows to the ends of the billets. As a result, it becomes necessary to introduce additional machining operations and metal waste increases. The article provides an analysis of existing methods of forming fins on a cylindrical surface. The authors analyze the advantages and disadvantages of applying the methods in modern conditions, select the most appropriate method, and substantiate the principles of developing tools for cold knurling of fins. The purpose of the work was to develop a tool for determining the forces acting in the cold knurling process and study their influence on the characteristics of the final products.